ANALISIS YURIDIS TERHADAP PEMBATASAN RUANG LINGKUP POLITIK UANG DALAM PEMILU DI INDONESIA - Emil Yadev; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In elections, there are several political parties, political parties (hereinafter referred to as political parties) are a necessity in modern democratic political life. As an organization, political parties are ideally intended to activate and mobilize the people, represent certain interests, provide compromises for competing opinions, and provide maximum political leadership to the maximum extent of legitimate and peaceful political leadership. the law is still unable to access the practice of money politics because of the weaknesses of the Perppu (Legislation) and the low level of law enforcement itself. A little idea from me, it is better if the vote recapitulation process is carried out directly at the Regency / City level to minimize money politics. The government should also be able to see and reduce what are the factors that make money politics happen, which factors include political factors, low institutionalization of political parties, oligarchic and transactional management of political parties, non-transparent financial system of political parties and accountable.This study examines the subject matter in accordance with the scope and identification of problems through a statute approach carried out by examining statutory regulations and regulations related to the legal issue under study. In this study, the authors conducted research on legal synchronization using descriptive methods. This esearch examines the juridical analysis of the limitations om the scope of money politics in elections in indonesia.The results of the research conducted by the author are, first, it is better if in Law Number 7 of 2017 concerning General Elections Article 523 is more explicitly explained about what other materials are, for example money politics in general elections, then achieving ideal arrangements regarding the boundaries of the scope of money politics , whereas the legal instrument for preventing money politics (money politics) in the election is already good, but it must be followed by serious socialization and legal counseling so that none of the prospective voters do not know the rules to be imposed on them in organizing the election.Keywords:Limitation-MoneyPolitic-Election